Penerapan Metode Casework dalam Meneliti Perkembangan Berhitung Siswa/i di Sekolah Dasar Negeri 060894 Medan Baru - Griselda, Rensina; Berlianti, Berlianti (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
Counting is one of the basic knowledge that must be acquired by the nation's generation who are still in school. This numeracy ability is useful for training children's general reasoning in dealing with a problem and children can process information and data that exist in everyday life. there are challenges nowadays, the impact of online learning since the covid-19 pandemic has made students not understand very clearly so that the subject matter received is not optimal which results in children's numeracy skills lacking. So in this case, the purpose of writing is to increase understanding in arithmetic in order to better understand and understand the basics of mathematics for everyday life. The location of the field work practice carried out by the author is on Jl. Rebab No. 99, Titi Chain, Kec. Medan Baru, Medan City, North Sumatra. With a total of 26 students. The campus teaching activities last for 3 months. The method used in this practical is the Casework method by Zastrow. The stages in the groupwork method include (1) Engagement, Intake, Contract, (2) Assessment, (3) Planning, (4) Intervention, (5) Monitoring, (6) Evaluation, and (7) Termination. The results of this practical activity showed an increase in learning and self-confidence of children in grades VI and IV at 060894 Public Elementary School. At the beginning of the meeting, the children had difficulty. After several meetings, the children began to be more fluent and dare to appear in front of the class to solve problems and explain how to solve them and there was an increase in grades in their school assignments.